The violence continuum : creating a safe school climate - Manvell, Elizabeth C., 1951- (R & L Education, 2012)
We expect schools to be a safe haven, but after more than a decade of targeted school violence prevention laws and safety plans, students are still marginalized and bullied to the point of despondence, retaliation, and even suicide. This thoughtful exploration of what makes a school a safe place is based on the understanding that violence is a continuum of acts and attitudes-subtle to overt-that have a negative effect on how students feel and learn.